2019
DOI: 10.1292/jvms.19-0228
|View full text |Cite
|
Sign up to set email alerts
|

Aerotolerance and multilocus sequence typing among <i>Campylobacter jejuni</i> strains isolated from humans, broiler chickens, and cattle in Miyazaki Prefecture, Japan

Abstract: Campylobacter jejuni is one of the leading causes of human gastroenteritis in Japan. As chickens and cattle are common reservoirs for C. jejuni , this microaerophilic, stress-sensitive bacterium can overcome and survive various stress conditions during zoonotic transmission, particularly foodborne, to humans. How C. jejuni overcomes stress conditions is, however, unclear. In the present study, 70 C. jejuni strains isolated from var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 40 publications
1
17
2
Order By: Relevance
“…In 2019, ST-21, ST-50, and ST-137 have been isolated from wild ducks, indicating their widespread distribution ( Wei et al, 2019 ). Three of the 10 STs (607, 443, and 51) were found in Japan and China ( Ozawa et al, 2016 ; Ma et al, 2017 ), while CC-460 and CC-607 have also been reported in samples from humans and cattle, indicating their threat to public health ( Ozawa et al, 2016 ; Kiatsomphob et al, 2019 ; Wei et al, 2019 ). CC-460 and CC-607 are thought to be virulent as they both possess many virulence genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, ST-21, ST-50, and ST-137 have been isolated from wild ducks, indicating their widespread distribution ( Wei et al, 2019 ). Three of the 10 STs (607, 443, and 51) were found in Japan and China ( Ozawa et al, 2016 ; Ma et al, 2017 ), while CC-460 and CC-607 have also been reported in samples from humans and cattle, indicating their threat to public health ( Ozawa et al, 2016 ; Kiatsomphob et al, 2019 ; Wei et al, 2019 ). CC-460 and CC-607 are thought to be virulent as they both possess many virulence genes.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, CC-21 is known as the prevalent clonal complex in human-derived C. jejuni isolates sharing a common genetic background and similar antimicrobial susceptibilities with C. jejuni strains from chicken ( Ohishi et al, 2017 ). CC-21 (ST-50 and ST-21) could be of interest in the region as it has been found in Korea, Japan, and China from humans, poultry, and cattle ( Ozawa et al, 2016 ; Oh et al, 2017 ; Kiatsomphob et al, 2019 ; Wei et al, 2019 ; Zhang et al, 2020 ). However, further studies are needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The housekeeping genes primer sequence of K. pneumoniae was shown in Table S2 . The PCR conditions were queried, and data were analyzed using the K. pneumoniae MLST website () (Joseph and Forsythe, 2017; Kiatsomphob et al, 2019; Shoaei et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Four C. jejuni strains (Penner serotypes and origins), AK1 (HS:3, chicken meat), B19 (untypable, cecum content of a broiler chicken), C65 (HS:4, rectal content of cattle) and H96 (HS:3, feces of a patient with enteritis), were used as a cocktail antigen for the ELISA and Western blotting assay. These strains were selected as representing the most dominant clonal complex (CC65) of multilocus sequence typing (MLST) observed in Miyazaki prefecture [11]. They were grown in Brucella agar (Becton, Dickinson and Company, Franklin Lakes, NJ, USA) at 37 °C for 18-24 hr under microaerobic conditions.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…ELISA was conducted to assess the IgG and IgA responses of female workers against C. jejuni. Due to the diversity of C. jejuni antigens, we used pooled samples of local strains that were the dominant MLST in Miyazaki prefecture among various sources [11] to provide soluble antigens for this assay. The use of such pooled samples has been standard practice for the development of broadly specific serological assays with considerable serotype heterogeneity [10].…”
Section: Workers In Chicken Processing Plants Are Considered To Be Atmentioning
confidence: 99%